On-Time Appointment Keeping and Associated Factors among Human Immunodeficiency Virus-Positive Adult Patients Accessing Antiretroviral Therapy at Health Centers in East Gojjam Zone, Northwest Ethiopia, 2019 - Mengistie Kassahun Tariku; Abebe Habtamu Belete; Daniel Tarekegn Worede; Sewnet Wongiel Misikir (AIDS Research and Treatment)
Background. The magnitude of on-time appointment keeping among HIV-positive adult patients was not identified in Ethiopia. Hence, this study aimed to assess on-time appointment keeping and associated factors among human immunodeficiency virus-positive patients accessing antiretroviral therapy in the East Gojjam Zone, Northwest Ethiopia. Methods. A community-based cross-sectional study was performed on 830 HIV-positive patients from April 1 to May 10, 2019, in East Gojjam Zone. A systematic random sampling technique was used to include study subjects, and data were collected through face-to-face interviews. Bivariable and multivariable binary logistic regression analyses were performed. Independent variables with a P value of <0.05 were considered statistically significant cut points. Results. The prevalence of on-time appointment keeping was 62.1%. Being >24 years old (adjusted odds ratio (AOR) = 2.13; 95% confidence interval (CI) = 1.54–4.25), being unmarried (AOR = 0.59; 95% CI = 0.45–0.82), taking a drug regimen of tenofovir + lamivudine (3TC) + efavirenz (EFV) (AOR = 2.11; 95% CI = 1.84–3.62), taking ART ≥12 months (AOR = 4.32; 95% CI = 2.22–8.40), having a mobile (AOR = 2.22; 95% CI = 1.44–3.64), and getting adherence support (AOR = 1.83; 95% CI = 1.16; 95% 1.16–3.50) were significant factors. Conclusion. On-time appointment keeping was low. Adherence support and appointment reminders should be strengthened.